Religious cultural Arts in mentality system of Javanese society: A critical analysis to the dynamics of ‘Keris’ development as a religious archaelogy - Mpu Tabah Chalifatah Aji; Nunuk Suryani; Akhmad Arif Musadad (Universitas Islam Sultan Agung, 2019)
Religion in a contextual meaning as a social practice contributes to the formation of religious cultural arts as well as religious archaeology. This research context discusses about ‘Keris’ as a form of religious cultural ideas and a full comprehension of the supernatural power outside the human himself (religiousness value). This research becomes significant to do since in the middle of global extremism lifting up again ‘Keris’ as a part of networking collective as a Javanese wisdom of life. Moreover the implication is that the religious philosophical value which is applied universally and symbolized in ‘Keris’ archaeology is able to lead to the realization of cultural identity which tightens nationalism in heterogeneity not homogeneity, creates awareness of the preservation of the religious archaeology as a form of religious cultural ideas. This research uses an ethnography qualitative research supported by interviews along with Talcon Parson’s the theory of Societies. It located in Solo, Jawa Tengah. The result of the study also shows that the dynamics of ‘Keris’ development genealogically is not only as a part of self-identity of Javanese society (invulnerability symbol). Kris in this case is also related to the society’s mentality system which is close to the philosophical value of religiousness which is fully comprehended as ethics and wisdom of life.